2012
DOI: 10.3174/ajnr.a3339
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Iterative Image Reconstruction in CT of the Paranasal Sinuses: A Phantom Study

Abstract: BACKGROUND AND PURPOSE: CT in low dose technique is the criterion standard imaging modality for evaluation of the paranasal sinus. Our aim was to evaluate the dose-reduction potential of a recently available sinogram-affirmed iterative reconstruction technique, regarding noise, image quality, and time duration when evaluating this region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 14 publications
(15 reference statements)
6
50
0
2
Order By: Relevance
“…Compared with the FBP reconstruction technique, all iterative reconstruction techniques increased SNR heterogeneously by 13%-88%, depending on the algorithm strength and tube current-time product. These results are similar to those of Schulz et al 12 for CT of the paranasal sinus and Leipsic et al 9 for coronary CT angiography. There was no significant difference for SNR between FBP and SAFIRE S1 for group 2 at 260 mAs.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Compared with the FBP reconstruction technique, all iterative reconstruction techniques increased SNR heterogeneously by 13%-88%, depending on the algorithm strength and tube current-time product. These results are similar to those of Schulz et al 12 for CT of the paranasal sinus and Leipsic et al 9 for coronary CT angiography. There was no significant difference for SNR between FBP and SAFIRE S1 for group 2 at 260 mAs.…”
Section: Discussionsupporting
confidence: 81%
“…Increased image blurring has been discussed in several publications that investigated iterative reconstruction techniques. 9,12,14,20,21 Silva et al 20 suggested that the diminished noise manifests as an oversmoothing of the images. Singh et al 8 thought that higher blending proportions of iterative reconstruction to FBP could substantially change the texture and characteristics of the images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Iterative reconstruction and special scanning techniques like high-pitch mode (HPM) and low-kilovolt scanning have further decreased radiation exposure. 4,6,7 Radiation exposure is considered a relevant issue because sinonasal disease may require repetitive imaging in a relatively young, otherwise healthy patient population with radiosensitive organs within the field of direct exposure (ie, eye lenses) or scattered x-rays (ie, thyroid gland).…”
Section: Abbreviationsmentioning
confidence: 99%
“…Lower tube voltage can provide better contrast because iodine preferentially absorbs much more photons at low tube voltage, but at lower tube voltage, images can be undesirably noisy [8][9][10][11] . Iterative reconstructions have been proven to reduce radiation dose notably, but can also alter the noise texture and obscure potential lesions of interest against a "waxy appearance" [5,7,11,12] . To optimize protocols, these tradeoffs should be carefully and conjunctively considered.…”
Section: Introductionmentioning
confidence: 99%